Voltametrija trdnih mikro delcev, imobiliziranih na površini grafitne elektrode - Kocijan, Aleksandra (Materiali in tehnologije, 2000)
The abrasive voltammetry was used for the study of the electrochemistry of microparticles of certain metals (Fe, Ni, Mo) and stainless steels (AISI 304L and 316L). The interest in these materials originates from their use in orthopaedic applications, where metal microparticles are released upon biodegradation of the orthopaedic implant.
Keywords: voltametrija; elektrokemijske lastnosti; železo; nikelj; molibden; nerjavno jeklo